Evaluation of Policy Regime in Waterfront City Development - Rahman, Abd. Rahman Syam (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The waterfront city concept is one of the coastal area-based development strategies that is often used to increase the attractiveness of the region, especially in Majene Regency. However, the successful implementation of this policy is highly dependent on collaboration between actors in the government regime. This research aims to evaluate how the policy regime in Majene Regency supports or hinders waterfront city development, using Clarence Stone's regime theory as an analytical framework. The research method uses a descriptive qualitative approach with in-depth interview techniques and policy document analysis. The results show that the policy regime in Majene Regency still faces major challenges, especially in terms of resource mobilization, division of roles between actors, and conflicts of interest. The main recommendation is the need to form a more inclusive governing coalition and strengthen local government capacity in managing resources and collaboration.